Pengaruh Bauran Komunikasi Pemasaran Terhadap Keputusan Pembelian (Studi Kasus pada Produk Mie Instant Indofood Semarang) - Latief, Muhammad Chaerul (Jurnal The Messenger, 2009)
The aim of the research to know the influence of the integrated communicationmarketing toward   the decision of purchasing  lndofood  instant noodles product  either partial  or simultant.  This research used survey method and the analysis   tool Double Regression.     It is  concluded  that,  as  a partial,  there  are four    of five  independent variables    which    have  a  significant    influence  toward  the  decision    of     consumer purchasing  Indofood noodles instant product.  These are advertising, personal selling, sales   promotion    and  public  relation.    Direct  marketing  doesn't    have  a  significant influence toward the decision of purchasing  lndofood noodles instant product. Simultaneously,  independent, variable has a significant influence toward the decision of a noodles instant product.